The Aspergillus nidulans Pbp1 homolog is required for normal sexual development and secondary metabolism - Soukup, Alexandra A. (Fungal Genet Biol, 2017)
P bodies and stress granules are RNA-containing structures governing mRNA degradation and translational arrest, respectively. Saccharomyces cerevisiae Pbp1 protein localizes to stress granules and promotes their formation and is involved in proper polyadenylation, suppression of RNA-DNA hybrids, and preventing aberrant rDNA recombination. A genetic screen for Aspergillus nidulans mutants aberrant in secondary metabolism identified the Pbp1 homolog, PbpA. Using Dcp1 (mRNA decapping) as a marker for P-body formation and FabM (Pab1, poly-A binding protein) to track stress granule accumulation, we examine the dynamics of RNA granule formation in A. nidulans cells lacking pub1, edc3, and pbpA. Although PbpA acts as a functional homolog of yeast PBP1, PbpA had little impact on either P-body or stress granule formation in A. nidulans in contrast to Pub1 and Edc3. However, we find that PbpA is critical for sexual development and its loss increases the production of some secondary metabolites including the carcinogen sterigmatocystin.